2020
DOI: 10.3390/ijms21176178
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Malignant Pleural Effusion Resident CD8+ T Cells from a Heterogeneous Collection of Tumors

Abstract: While T cell-based cancer immunotherapies have shown great promise, there remains a need to understand how individual metastatic tumor environments impart local T cell dysfunction. At advanced stages, cancers that metastasize to the pleural space can result in a malignant pleural effusion (MPE) that harbors abundant tumor and immune cells, often exceeding 108 leukocytes per liter. Unlike other metastatic sites, MPEs are readily and repeatedly accessible via indwelling catheters, providing an opportunity to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Despite this abundance of CD4 + T cells, several studies have shown that the CD4 + /CD8 + T cell ratio in MPEs is similar to matched peripheral blood samples in patients with mesothelioma (54,62). For lung cancer patients, CD8 + T cell frequencies were greater in the peripheral blood compared to the MPE for one study (53) but were similar between both compartments in others (41,63), suggesting CD8 + T cell infiltration in the pleural space may be more cancer or chemotherapy specific.…”
Section: Mpe Are Enriched With T Cellsmentioning
confidence: 96%
See 4 more Smart Citations
“…Despite this abundance of CD4 + T cells, several studies have shown that the CD4 + /CD8 + T cell ratio in MPEs is similar to matched peripheral blood samples in patients with mesothelioma (54,62). For lung cancer patients, CD8 + T cell frequencies were greater in the peripheral blood compared to the MPE for one study (53) but were similar between both compartments in others (41,63), suggesting CD8 + T cell infiltration in the pleural space may be more cancer or chemotherapy specific.…”
Section: Mpe Are Enriched With T Cellsmentioning
confidence: 96%
“…The proportion of total T cells in the MPE is greater than in matched peripheral blood samples from both mesothelioma and lung cancer patients ( 53 , 54 ). CD4 + T cells are the predominant T cell subset in MPE both prior to and after chemotherapy ( 41 , 54 57 ). Of these CD4 + T cells, an increased proportion of regulatory T cells (CD4 + CD25 + ) are recruited in MPEs by chemokines and pro-inflammatory cytokines, compared to matched peripheral blood ( 58 61 ).…”
Section: Cellular Characteristics Of Malignant Pleural Effusions Without Icbmentioning
confidence: 99%
See 3 more Smart Citations